Kant's Deduction of the Categories - Watt, R (2013)
This thesis defends an interpretation of the argument that Immanuel Kant calls his Transcendental Deduction of the Categories. It is divided into four chapters. The subject of the first chapter is the aim of Kant’s Deduction of the Categories. It is argued that what Kant has set out to find is an answer to the question how it is that the Categories are able to serve as representations of objects. This chapter also includes a detailed account of what Kant thinks is required for a concept to serve as a representation of an object. The subject of the second chapter is the strategy of Kant’s Deduction of the Categories. It is argued that what Kant thinks he needs to do in order to deduce the Categories is to show that an object must conform to the Categories if we are to make a judgment about this object. The third chapter is concerned with the central claim of Kant’s Deduction of the Categories, viz. the Principle of the Original Synthetic Unity of Apperception. It is argued that this principle consists in the claim that if we are to make a judgment about an object then we must be able to achieve a special sort of consciousness – specifically, the consciousness of what Kant calls the necessary unity of synthesis. The fourth and final chapter of the thesis is concerned with Kant’s justification for the Principle of the Original Synthetic Unity of Apperception. It is argued that Kant’s commitment to this principle is based on his recognition of a key fact about an act of judgment, viz. the fact that in making a judgment about an object, part of what we think is that our representations ought to be connected in a particular way.